TRACER STUDY TOLOK UKUR KUALIFIKASI MADRASAH - Siti Aimah; Qoni’ Wanda Nurfitria (Institut Agama Islam Darussalam Blokagung, 2023)
The purpose of this research is to find out; the implementation, function, and management objectives of the alumni empowerment strategy through tracer study activities and their evaluation; Research location: Madrasah Aliyah al-Amiriyyah Blokagung. The research method used is descriptive qualitative. Collecting data through observation, interviews, and documentation. Data analysis techniques using data reduction, data presentation, and drawing conclusions. The results of the study: implementation of the management strategy for empowering alumni: (a) Forming a family of alumni in the year of graduation; (b) Forming an alumni management for all members; (c) Appoint alumni who have a national reputation as alumni leaders; (d) Involve outstanding alumni in the publication of acceptance of new students; (e) Inviting alumni to events held both competitions and birthdays; (f) Presenting reputable alumni as motivators and fillers for activities. The functions and objectives of the management strategy for alumni empowerment are: (a) Evaluating tracer study activities as part of alumni empowerment in each graduate to measure the success of the implemented educational curriculum; (b) The need to review the educational curriculum so that it is able to achieve educational goals as expected by stakeholders; (c) monitoring the development of alumni as madrasah ambassadors for the community and government; (d) Monitoring results as a basis for activities to increase alumni activities that contribute to the development of educational quality. While the evaluation of tracer study activities is through (a) Drawing up a yearly alumni chart containing alumni identities and their activities; (b) holding meetings with alumni which are used to strengthen friendship as well as measure loyalty to the madrasah; (e) accommodate the messages and impressions of alumni to improve the quality of madrasas through a tracer study in the form of a google form application that can be accessed widely; (d) recruit alumni with high achievements and high loyalty as part of Madrasa management.